Analytically Modeling the Asymmetric Double Gate Tunnel FET. (27th March 2015) - Lv, Hongfei; Sato, Shingo; Omura, Yasuhisa; Mallik, Abhijit
Abstract : This paper proposes an analytical model for the asymmetric double gate (ADG) TFET. The two-dimensional Poisson equation is solved based on a depletion approximation. The two-dimensional potential function is given by appropriate boundary conditions. Internal electric field is calculated from the potential model and the tunnel current is numerically calculated using Kane's tunnel current generation model. We use a commercial TCAD simulator to examine the analytical model.